Palatine rugoscopy and its challenges in human identification: an integrative review (Research, Society and Development, 2021)
This integrative review aimed to verify how the identification of Forensic Dentistry, by means palatal wrinkles, has been presented in the scientific literature and which are the limitations for its use in post mortem forensics. That required a search under the following descriptors: Palatal Rugoscopy, Palatoscopy and Forensic Dentistry, in the databases of Pubmed, BVS (Medline and Lilacs), BBO and Scielo for published articles among 2010 to 2019. Those that were available with full and free text in Portuguese and English languages whose conclusion was according to the purpose of this study, leaving out the articles related to live and ante mortem forensics, as well as the repeated ones. From a total of 58 Articles counted, 7 met fully the inclusion /exclusion criteria. These articles puntuacted reviews of narrative, sistematic literature and meta-analysis, forensic case reports and review of these cases. It can be concluded that Palatal Rugoscopy has been presented in the scientific literature as a useful guide in human identification, applied, usually, as a complementary method, but still can provide many additional information; However, should not be used as the only method of identifying the victim, once that also has many noted limitations that can difficult or even to make the identification unfeasible.